Impact of digital financial inclusion on compliance with tax obligations in Peru 2020 – 2023 - López Paredes, Gabriel; Carrasco Pariamachi, Liesly (mktDESCUBRE, 2024)
The objective of this article was to establish the impact of digital financial inclusion on compliance with tax obligations in Peru from 2020 to 2023. Digital banking promotes financial inclusion through access to formal financial services and contributes to greater clarity in the operations carried out. The COVID-19 pandemic precipitated the implementation of digital technology, which led to increased use of digital financial services. The methodological approach was quantitative, descriptive, correlational, and longitudinal because statistical data issued by the SBS, MEF, and SUNAT were analyzed between 2020 and 2023. The results showed an increase in digital operations, which has improved compliance with tax obligations, which demonstrates the existence of a high and very significant correlation (r = 0.723) between the variables studied, in the sense that digital financial inclusion impacts compliance with tax obligations in Peru. It is concluded that the increase in financial incorporation contributes to improving tax compliance because it facilitates the registration and traceability of economic transactions.